2015
DOI: 10.1117/1.jmm.14.2.024501
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of resistive switching behavior of Ag/SnOx/ITO device

Abstract: SnO x thin film was deposited by reactive magnetron sputtering and the resistance switching behavior of Ag∕SnO x ∕ITO was investigated. The endurance testing indicates that HRS resistance decreases with an increase in the number of cycles. After annealing, the memory performance is enhanced, and the ratio of the device resistance of HRS and LRS increases greatly. The abnormal transformation sequence from HRS to LRS was observed for the annealed device and can be explained by electron trapping and detrapping ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Unlike conventional SnO X , which demands an annealing process to achieve resistive switching (RS) characteristics, the as-deposited SnO X used in this paper showed RS characteristics. As-deposited SnO X by direct current (DC) reactive magnetron sputtering has already been verified the RS in a Ag/SnO X /ITO device by Da chen and Shi-Hua Huang, and it showed a low resistance of less than 3 kΩ and a resistance window of less than ~10 [ 13 , 14 ]. In addition, Jidong Jin et al reported that the DC-sputtered SnO X showed poor RS on the stack of an Al/SnO X /Pt device [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike conventional SnO X , which demands an annealing process to achieve resistive switching (RS) characteristics, the as-deposited SnO X used in this paper showed RS characteristics. As-deposited SnO X by direct current (DC) reactive magnetron sputtering has already been verified the RS in a Ag/SnO X /ITO device by Da chen and Shi-Hua Huang, and it showed a low resistance of less than 3 kΩ and a resistance window of less than ~10 [ 13 , 14 ]. In addition, Jidong Jin et al reported that the DC-sputtered SnO X showed poor RS on the stack of an Al/SnO X /Pt device [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The difference between the two kinds of RS effects is whether they have two stable resistance states without external applied bias. [3][4][5][6][7] Furthermore, investigating the RS mechanism of different RS methods is significant to clarify the RS behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Yun et al (Ag/SnO 2 /Pt) reported that microwave treatment influences the diameter of the filament, which in turn increases the formation and rupture times of the filament for improved stability. Chen et al investigated RS behaviour for Ag/SnO x /ITO structure to observe the impact of annealing on the ratio of the resistances states, as it affects the memory performance 34 , 35 . However, SnO x based RRAM devices operating compliance-free and exhibiting stable multistate operation are very scarcely reported.…”
Section: Introductionmentioning
confidence: 99%